THE ROLE OF APPLIED MATHEMATIC SUBJECTS IN ECONOMIST’S EDUCATION - Natalia V. Popova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article touches upon the problem of improving the quality of mathematic training of economics universities graduates, which is  connected with the necessity of using mathematic methods in analyzing and forecasting economy within  the frames of Russian economy passing over to market relations.  The review of investigations dealing with this problem shows certain  difficulties for its solution. The author analyzes the role of applied economics and mathematic subjects in economist’s education by using the subject ‘Mathematic Methods of Finance Analysis’ as an  example. The principle conclusion drawn by the author: applied  mathematic subjects based on fundamental sections of mathematics  continues mathematic education of the economist , which could  improve the level of mathematic training of future economists and the quality of economics education in general.